Long-term low-dose acetylsalicylic use shows protective potential for the development of both vascular dementia and Alzheimer’s disease in patients with coronary heart disease but not in other individuals from the general population: results from two large cohort studies - Nguyen, Thi Ngoc Mai; Chen, Li-Ju; Trares, Kira; Stocker, Hannah; Holleczek, Bernd; Beyreuther, Konrad; Brenner, Hermann; Schöttker, Ben (Alzheimer's research & therapy, 2022)
No population-based cohort study investigated a potential inverse association between long-term low-dose acetylsalicylic acid (ASA) use and all-cause dementia and its two most common sub-types Alzheimer’s disease (AD) and vascular dementia (VD) so far.
Gesehen am 07.07.2022